Further investigation on microstructure refinement of internal crack initiation region in VHCF regime of high-strength steels - Yukun Chang; Liang Zheng; Xiangnan Pan; Youshi Hong (Fracture and Structural Integrity)
The profile samples prepared by focused ion beam (FIB) in crack initiation region (CIR) and fish-eye (FiE) region of failed specimens subjected to rotary bending (RB) and ultrasonic axial (UL) fatigue testing with various stress ratios (R) were observed by transmission electron microscopy (TEM) with selected area electron diffraction (SAD) detection for two high-strength steels. The grain size and the thickness of nanograin layer along the crack growth path in CIR underneath fine-granular-area (FGA) were measured for the cases of R < 0, and a normalized quantity d* based on the detected SAD patterns was introduced to quantitatively demonstrate the variation of the grain size. The results showed that the nanograin size near the origin (an inclusion) of crack initiation is smaller than that away from the inclusion. Nevertheless, there was no evidence of grain refinement in CIR for the cases of R > 0 and the FiE region outside CIR for either negative or positive stress ratio cases, which suggests that the formation of nanograin layer in the FGA region is due to the numerous cyclic pressing (NCP) process and the plastic deformation ahead of the crack tip may cause certain extent of microstructure deformation but is insufficient to form nanograin layer on crack surfaces.